Electrical stimulation or tacrolimus (FK506) alone enhances nerve regeneration and recovery after nerve surgery, while dual use reduces variance and combines strengths of each in promoting enhanced outcomes. Issue 1 (22nd November 2022) - Marsh, Evan B.; Schellhardt, Lauren; Hunter, Daniel A.; Mackinnon, Susan E.; Snyder‐Warwick, Alison K.; Wood, Matthew D.
Abstract: Introduction/Aims: Repaired nerve injuries can fail to achieve functional recovery. Therapeutic options beyond surgery, such as systemic tacrolimus (FK506) and electrical stimulation (E‐stim), can improve recovery. We tested whether dual administration of FK506 and E‐stim enhances regeneration and recovery more than either therapeutic alone. Methods: Rats were randomized to four groups: E‐stim, FK506, FK506 + E‐stim, and repair alone. All groups underwent tibial nerve transection and repair. Two sets of animals were created to measure outcomes of early nerve regeneration using nerve histology (n = 36) and functional recovery (n = 42) (21‐ and 42‐day endpoints, respectively). Functional recovery was measured by behavioral analyses (walking track and grid walk) and, at the endpoint, muscle mass and force. Results: Dual E‐stim and FK506 administration produced histomorphometric measurements of nerve regeneration no different than either therapeutic alone. All treatments were superior to repair alone (FK506, P < .0001; E‐stim, P < .05; FK506 + E‐stim, P < .05). The E‐stim and FK506 + E‐stim groups had improved behavioral recovery compared with repair alone (at 6 weeks: E‐stim, P < .05; FK506 + E‐stim, P < .01). The FK506 group had improved recovery based on walking‐track analysis (at 6 weeks: P < .001) and muscle force and mass ( P < .05). The concurrent use of both therapies ensured earlier functional recovery and decreased variability in functional outcomes compared with either therapy alone, suggesting a moderate benefit. Discussion: Dual administration of FK506 and E‐stim showed minimal additive effects to further improve regeneration or recovery compared with either therapy alone. The data suggest the combination of FK506 and E‐stim appears to combine the relative strengths of each therapeutic. Abstract : Repaired nerve injuries can fail to achieve functional recovery. We tested whether dual administration of FK506 and E‐stim further enhance regeneration and recovery. Two sets of rats nerve injury and repair models were measured for outcomes of early nerve regeneration and functional recovery. While dual administration of FK506 and E‐stim showed minimal additive effects compared to either therapy alone in regeneration or recovery, the concurrent use of both therapies ensured earlier functional recovery and decreased variability in outcomes.